2022
DOI: 10.3390/su142215019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interventions Based on Achievement Goals and Self-Determination Theories on the Intention to Be Physically Active of Physical Education Students: A Systematic Review and Meta-Analysis

Abstract: The aim was to review the effects of interventions based on self-determination theory and achievement goals theory on intention to be physically active in the future in physical education students, as well as to conduct a meta-analysis to determine the overall effect size of these interventions. PRISMA guidelines were followed to conduct this systematic review and meta-analysis. Three scientific electronic databases were used: Web of Science (WOS), Scopus, and SportDiscus. A total of eleven studies fulfilled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The findings reported the importance of satisfying the BPNs, especially perceived competence, to improve participation rates in invasion sports with health benefits (active lifestyle). In turn, Fernández-Espínola, Almagro, Tamayo-Fajardo, Paramio-Pérez and Saénz-López [4] indicated that the involvement of families could also influence the promotion of physical activity in children and adolescents, therefore, this should be taken into account in future research.…”
Section: Bpnsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings reported the importance of satisfying the BPNs, especially perceived competence, to improve participation rates in invasion sports with health benefits (active lifestyle). In turn, Fernández-Espínola, Almagro, Tamayo-Fajardo, Paramio-Pérez and Saénz-López [4] indicated that the involvement of families could also influence the promotion of physical activity in children and adolescents, therefore, this should be taken into account in future research.…”
Section: Bpnsmentioning
confidence: 99%
“…Interventions based on the Self-Determination Theory could be useful in the process of promotion and adherence to, physical activity [4]. Thus, the satisfaction of three BPNs by students or players leads to an increase in intrinsic motivation, the most self-determined regulation, which causes students or players to engage in a sport modality on their own initiative (e.g., involvement in a sport for pleasure, fun, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Interventions based on the SDT could be useful in the process of promotion and adherence to PA [4]. Thus, the satisfaction of three BPNs by students or players leads to an increase in intrinsic motivation, the most self-determined regulation, which causes students or players to engage in a sport modality on their own initiative (e.g., involvement in a sport for pleasure, fun, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons for this lack of interest/motivation could be linked to the model applied by the teacher, who in turn should consider the heterogeneity of the group-classes. This type of studies contribute of students contribute to the sustainability of the educational, social and health systems, since they provide knowledge of the influence of psychological variables for the promotion of PA in and out of school [4], with health benefits by avoiding sedentary lifestyles and their consequences. Thus, this study aimed to analyze whether students' gender and sport experience, and teaching model influence the psychological variables (BPNs and adherence to sport) when teaching school soccer and basketball.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that achievement goal orientations are modifiable using interventions aimed at the school environment, including whole-school approaches. 14–16 Students’ achievement goal orientations are thought to be influenced by whether schools emphasise learning and personal growth (i.e., mastery goals) or competition and social comparison (i.e., performance goals). 15 Interventions that aim to alter achievement goal orientations have therefore been aimed at school policies, teaching practices and organisational structures, to create environments that promote mastery goals and de-emphasize performance goals 15 .…”
Section: Introductionmentioning
confidence: 99%